Metallic micro and nano materials fabrication with atomic diffusion - Saka, Masumi (Engineering Materials., 2011)
This book focuses on the metallic Nano- and Micro-materials (NMMs) fabricated by physical techniques such as atomic diffusion. A new technology for fabricating NMMs by atomic diffusion is presented. Two kinds of atomic diffusion are treated; one is a phenomenon caused by electron flow in high density and called electromigration and the other is stress migration which depends on a gradient of hydrostatic stress in a material. In three parts, the book describes the theory of atomic diffusion, the evaluation of physical properties and the treatment and applications of metallic NMMs. The new methods such as atomic diffusion are expected are expected to be crucial for the fabrication of NMMs in the future and to partially replace methods based on chemical reactions.